Internal audit effectiveness in Libyan fully owned oil and petroleum companies: the moderating role of continuous learning - Hasan, Mustafa A Abduenabe (2019)
The main purpose of the current study is to determine the factors that impact on internal audit effectiveness (IAE). In addition, the moderating effect of continuous learning on the relationship between internal auditors’ independence, top management support, relationship with external auditors, audit committee and auditees, funding and internal audit effectiveness is tested using empirical data. The contingency and agency theory are used to support the framework of the current research. Data was collected from internal auditors of oil and petroleum companies operating in Libya using a self-administered questionnaire. The collected data was analysed using SPSS by employing exploratory factor analysis (EFA) for selecting items of measurements. After preliminary data analysis and EFA, a sample of 126 internal auditors was used to test the proposed hypotheses with the help of multiple regression analysis. In addition to that, hierarchical multiple regression was employed to test the moderating effect of continuous learning on IAE. The results indicate that among the factors, internal auditors’ independence, top management support, relationship with external auditors, audit committee and auditees and funding, significantly influence IAE. Moreover, continuous learning significantly moderates the relationship between relationship with the auditees and external auditors and IAE in Libyan Fully Owned Oil and Petroleum Companies. This study contributes to the existing literature in the field of IAE and extends the application of the contingency and agency theories in the context of oil and petroleum companies. The results of the study can be used to enhance IAE, in general, and in oil and petroleum companies, in particular. The chief financial officers can use these results to enhance IAE and provide continuous learning to their internal auditors. This study provides several suggestions on how future studies can extend the current framework to uplift the knowledge related to auditing, especially internal auditing.